Infrastructure communication in international relations - Van Noort, Carolijn (New York, NY : Routledge, 2021)
"This book demonstrates how infrastructure projects and communications thereof are strategized by rising powers to envision progress, to improve the actor's international identity, and to substantiate and leverage the actor's vision of international order. While the physical aspects of infrastructure are important, infrastructure communication in International Relations demands more scholarly attention. Using a case study approach, Carolijn van Noort examines how rising powers communicate about infrastructure internationally and discusses the significance of these communication practices. The four case studies include BRICS's summit communications about infrastructure, Brazil's infrastructure promises to Africa, China's communication of the Belt and Road Initiative in East Africa, and Kazakh's news media coverage of China's Belt and Road Initiative. Van Noort highlights the fact that the link between infrastructure, identity, and order-making is arbitrary and thus contested in practice, with rising powers operationalizing infrastructure communication in international relations in varied ways. She argues that both communication organization and the visuality of strategic narratives on infrastructure influence the international communication of infrastructure vision and action plans with different levels of success. Infrastructure Communication in International Relations is a welcome and timely book of interest to students and scholars in the field of International Relations, global communications, and the politics of infrastructure"--
Strategic narratives on infrastructure -- BRICS and infrastructure -- Brazil, Africa and infrastructure -- China, East Africa and the Belt and Road Initiative -- Kazakhstan, China and the Belt and Road Initiative.
OCLC-licensed vendor bibliographic record.
Keywords: Infrastructure (Economics) -- Political aspects -- BRIC countries; Communication in international relations -- BRIC countries; BRIC countries -- Foreign relations; BRIC countries -- Foreign economic relations; POLITICAL SCIENCE / International Relations / General